Intrathecal Catheter Use After Accidental Dural Puncture in Obstetric Patients: Literature Review and Clinical Management Recommendations. Issue 3 (24th September 2022) - Orbach-Zinger, S.; Jadon, A.; Lucas, D. N.; Sia, A. T.; Tsen, L. C.; Van de Velde, M.; Heesen, M.
Abstract : ( Anaesthesia . 2021;76:1111–1121) In the event of an accidental dural puncture (ADP) the epidural can be either resited or a catheter can be inserted intrathecally for use as a continuous spinal (intrathecal, IT) catheter, thus eliminating the need for needle reinsertion. An IT catheter may also permit swift labor analgesia and facilitate cesarean delivery anesthesia. However, clinical management of IT catheters for labor analgesia is not without risk of adverse effects. Accordingly, this review evaluates recent studies on IT catheters for parturients, including the management and quality of analgesia and anesthesia, the effect on postdural puncture headache (PDPH) risk, obstacles to use, and deficiencies in our current understanding.